Quo Vadis Legal Protection for Victims of Sexual Violence against Children in Indonesia: Discourse on Legal Justice (Law Research Review Quarterly, 2022)
Laws in Indonesia that ensnare perpetrators of pedophilic practices are considered by many experts to be not serious. So that the punishment for pedophiles is not commensurate with what has been done and the risk of damaging the victim's future. In addition, protection from society for victims of pedophilia is also lacking. Public attention, especially in the context of children, is currently more focused on children's behavior that violates the rule of law, criminal behavior committed by children. But with regard to the problem of children who are victims, especially in cases of sexual violence, it rarely gets attention. This study aims to analyze the protection for child victims of sexual violence in Indonesia by using various comparisons of related laws and regulations, be it human rights laws, child protection laws, juvenile justice laws, to various other legal rules.